Socially Prescribed Perfectionism - AlKandari, Essa (2025)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Essa AlKandari entitled, “Socially Prescribed Perfectionism”, submitted in April 2025. Thesis advisor is Dr. Phillip McCarthy and thesis co-advisor is Dr. Maria Eleftheriou. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).